2014
DOI: 10.5125/jkaoms.2014.40.6.266
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction plates used in the surgery for mandibular discontinuity defect

Abstract: ObjectivesThe purpose of this study was to analyze the survival rate of reconstruction plates that were used to correct mandibular discontinuity defects.Materials and MethodsWe analyzed clinical and radiological data of 36 patients. Only discontinuous mandibular defect cases were included in the study. Reconstruction plate survival rate was analyzed according to age, gender, location of defect, defect size, and whether the patient underwent a bone graft procedure, coronoidectomy, and/or postoperative radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 22 publications
0
31
0
2
Order By: Relevance
“…However, radiation exposure compromises the integrity of the recipient vessels and negatively affects free flap viability, with both preoperative and postoperative radiotherapy being associated with increased flap complication rates . Furthermore, plate reconstruction after RT is also associated with many late complications, and Seol et al have reported a significant decrease in the success of plate reconstruction among patients who underwent postoperative RT . In the present study, plate failure occurred in 1 of 3 patients who underwent mandibular bone reconstruction, which suggests that plate‐based mandibular bone reconstruction may have limited effectiveness and should be carefully considered after C‐ion RT.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, radiation exposure compromises the integrity of the recipient vessels and negatively affects free flap viability, with both preoperative and postoperative radiotherapy being associated with increased flap complication rates . Furthermore, plate reconstruction after RT is also associated with many late complications, and Seol et al have reported a significant decrease in the success of plate reconstruction among patients who underwent postoperative RT . In the present study, plate failure occurred in 1 of 3 patients who underwent mandibular bone reconstruction, which suggests that plate‐based mandibular bone reconstruction may have limited effectiveness and should be carefully considered after C‐ion RT.…”
Section: Discussionmentioning
confidence: 62%
“…21 Furthermore, plate reconstruction after RT is also associated with many late complications, and Seol et al have reported a significant decrease in the success of plate reconstruction among patients who underwent postoperative RT. 22 In the present study, plate failure occurred in 1 of 3 patients who underwent mandibular bone reconstruction, which suggests that plate-based mandibular bone reconstruction may have limited effectiveness and should be carefully considered after Cion RT. Nevertheless, the patient who experienced reconstruction failure had successful soft tissue transplantation without any major complications and preserved masticatory and deglutitive functions (because of the soft-tissue free flap and prosthesis).…”
Section: Discussionmentioning
confidence: 64%
“…The success rate of mandibular reconstruction has increased because of improvements in plate designing and materials. However, plate-related complications still develop frequently and can sometimes cause serious problems to patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction plates are provided in straight and slightly thicker and stiffer pre-curved lengths. They have oval screw holes, like mentioned compression plates, and they allow potential limited compression [22,23]. To create so-called personalized geometrical models of the plates, which fit anatomy of the traumatized region of the mandible, there is a need to use geometrical model of the patient's mandible as a base model that shape of plate should follow [24].…”
Section: Parametric Model Of Plate Implantsmentioning
confidence: 99%